2020
DOI: 10.1002/humu.23970
|View full text |Cite
|
Sign up to set email alerts
|

Further delineation of putative ACTB loss‐of‐function variants: A 4‐patient series

Abstract: ACTB encodes β‐cytoplasmic actin, an essential component of the cytoskeleton. Based on chromosome 7p22.1 deletions that include the ACTB locus and on rare truncating ACTB variants, a phenotype resulting from ACTB haploinsufficiency was recently proposed. We report putative ACTB loss‐of‐function variants in four patients. To the best of our knowledge, we report the first 7p22.1 microdeletion confined to ACTB and the second ACTB frameshifting mutation that predicts mRNA decay. A de‐novo ACTB p.(Gly302Ala) mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In addition, we found that the expressions of ACTB mRNA and protein were not significantly altered in patients compared with normal controls. This is consistent with the previously reported p.Arg183Trp ( Procaccio et al, 2006 ), p.Arg196His ( Rivière et al, 2012 ), and p.Gly302Ala ( Baumann et al, 2020 ) variants. Thus, we infer that the variant caused the disorder by gain‐of‐function or dominant‐negative mechanisms ( Rivière et al, 2012 ; Di Donato et al, 2014 ; Verloes et al, 2015 ; Baumann et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, we found that the expressions of ACTB mRNA and protein were not significantly altered in patients compared with normal controls. This is consistent with the previously reported p.Arg183Trp ( Procaccio et al, 2006 ), p.Arg196His ( Rivière et al, 2012 ), and p.Gly302Ala ( Baumann et al, 2020 ) variants. Thus, we infer that the variant caused the disorder by gain‐of‐function or dominant‐negative mechanisms ( Rivière et al, 2012 ; Di Donato et al, 2014 ; Verloes et al, 2015 ; Baumann et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the previously reported p.Arg183Trp ( Procaccio et al, 2006 ), p.Arg196His ( Rivière et al, 2012 ), and p.Gly302Ala ( Baumann et al, 2020 ) variants. Thus, we infer that the variant caused the disorder by gain‐of‐function or dominant‐negative mechanisms ( Rivière et al, 2012 ; Di Donato et al, 2014 ; Verloes et al, 2015 ; Baumann et al, 2020 ). The correlation between ACTB genotype and phenotype, and the underlying pathogenesis needs to be further determined.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations